Applied Regional Economic Research Can Improve Development Strategies and Drive Better Outcomes. Issue 1 (February 2023) - Poole, Kenneth E.; Forbes, Allison; Williams, Nichelle
The COVID-19 pandemic brought about an unimagined level of federal investment in regional economic development and much greater political attention to its priorities. Economic development researchers have an opportunity to contribute to an array of federally funded and pandemic-inspired regional experiments, many of which reflect shifting concerns about economic development and what constitutes success. Among these include the importance of addressing historical racial, ethnic, and gender inequalities; the value of research and development as a solution to major human problems; the severity of impending workforce shortages in key sectors; the fragility of many highly efficient global supply chains; and the inadequacy of our underinvested economic data infrastructure to help understand these issues. Researchers have a unique opportunity to examine the regional impacts of national issues by improving public investment logic models, advocating for an improved data infrastructure, and providing evidence to address the long-standing tension between growth and equity as competing economic development priorities.